Effectiveness of School Management in Increasing Teacher Job Satisfaction in the Digitalization Era - Rosmiati Rosmiati; Neviaisyah Neviaisyah (Pt. Anagata Sembagi Education, 2025)
This study aims to describe in depth the effectiveness of school management in improving teacher job satisfaction in the era of digitalization of education. In the face of increasingly massive technological transformation, schools are required to implement responsive and adaptive managerial strategies. The research approach used is descriptive qualitative, with data collection techniques through documentation studies and literature review of various relevant previous research results. The main focus of this study includes the identification of technology-based management strategies, the leadership role of school principals in initiating and directing change, and the analysis of supporting and inhibiting factors that directly or indirectly affect the level of teacher job satisfaction. The data analysis process was conducted using thematic analysis to identify patterns, themes and relationships between managerial elements in the context of digitalisation. The results show that the effectiveness of school management is strongly influenced by the readiness of adequate digital infrastructure, the availability of continuous information and communication technology (ICT) training, the use of an integrated school management information system, and the visionary, collaborative and participatory leadership style of the school principal. However, a number of challenges remain, including limited supporting facilities, increased workload due to digital administrative demands, and an uneven gap in digital skills among teachers. These findings provide an important contribution to formulating the direction of educational managerial policies that not only adapt to technological developments, but are also oriented towards the welfare and work motivation of teachers as the spearhead of the implementation of education in schools.